Cobalt Oxide Supercapacitor Electrode Recovered from Spent Lithium-Ion Battery - Aboelazm, Eslam A. A.; Ali, Gomaa A. M.; K. F., Chong (ISSR Publishing, 2018)
In this study, cobalt oxide from spent lithium-ion batteries has been successfully recovered using the electrodeposition process. XRD showed the formation of Co3O4 phase and XPS showed two significant peaks of Co3O4 correlated to Co 2p1/2 and Co 2p3/2 and a significant peak which is related to Co3O4 correlated to O 1S. FTIR spectra showed two stretching bands Co(III)-O and Co(II)-O confirms the material composition of Co3O4. The electrodeposited material showed porous sheets-like morphology. The specific capacitance was found to be 143 F/g at a current density of 0.5 A/g.